A detailed examination of platelet function inhibition by nitric oxide in platelet-rich plasma and whole blood - Zimmermann, Robert; Krüger, Julia; Filipovic, Milos; Ivanovic-Burmazovic, Ivana; Calatzis, Andreas; Eckstein, Reinhold; Weiss, Dominik R. (Clinical Laboratory, 2013)
Background: The question of whether novel instruments such as multiple electrode aggregometry (MEA) can be used for measurement of the effects of nitric oxide (NO) on platelets (PLTs) has not been examined. Methods: Therefore, we compared the effects of NO concentrations (1, 10, and 100 μM) on the PLT aggregation response to ADP, arachidonic acid (AA), collagen, ristocetin, and thrombin receptor-activating peptide 6 (TRAP-6) using light transmission aggregometry (LTA) and multiple electrode aggregometry (MEA) and examined the effects of NO using the platelet function analyzer (PFA)-100™. Results: The response of PLTs to ADP and AA was strongly inhibited by all NO concentrations in LTA and MEA. The inhibition of the responses to ristocetin and collagen was detectable in MEA at lower NO concentrations than in LTA. However, the typically increasing lag phase between collagen addition and the aggregation response in the presence of NO was more obvious in LTA. TRAP caused a reproducible early response in the presence of NO in LTA which was followed by rapid PLT disaggregation, whereas even 100 μM NO did not inhibit the response to TRAP in MEA. Finally, NO prolonged the in-vitro bleeding time remarkably more in the PFA-100 collagen-epinephrin cartridge than in the collagen-ADP cartridge. Conclusions: Whole blood versus PLT rich plasma, citrate versus hirudin, and high versus low shear influenced the effects of NO. This shows that a careful selection of models and potentially a combination of different methods is appropriate for a differentiated evaluation of pharmacological or physiological mechanisms of NO-donors or of NO-inhibitors.

Amino acids as possible alternative nitrogen source for growth of Euglena gracilis Z in life support systems - Richter, Peter; Liu, Y.; An, Y.; Li, X.; Nasir, Adeel; Strauch, Sebastian; Becker, Ina; Krüger, Julia; Schuster, Martin; Ntefidou, Maria; Daiker, Viktor; Haag, Ferdinand; et al. (Life Sciences in Space Research, 2015)
In recent times Euglena gracilis Z was employed as primary producer in closed environmental life-support system (CELSS), e.g. in space research. The photosynthetic unicellular flagellate is not capable of utilizing nitrate, nitrite, and urea as nitrogen source. Therefore, ammonium is supplied as an N-source in the lab (provided as diammonium-dihydrogenphosphate, (NH)HPO) to E. gracilis cultures. While nitrate exerts low toxicity to organisms, ammonium is harmful for many aquatic organisms especially, at high pH-values, which causes the ionic NH4+ (low toxicity) to be partially transformed into the highly toxic ammonia, NH. In earlier reports, Euglena gracilis was described to grow with various amino acids as sole N-source. Our aim was to investigate alternatives for (NH)HPO as N-source with lower toxicity for organisms co-cultivated with Euglena in a CELSS. The growth kinetics of Euglena gracilis cultures was determined in the presence of different amino acids (glycine, glutamine, glutamic acid, leucine, and threonine). In addition, uptake of those amino acids by the cells was measured. Cell growth in the presence of glycine and glutamine was quite comparable to the growth in (NH)HPO containing cultures while a delay in growth was observed in the presence of leucine and threonine. Unlike, aforementioned amino acids glutamate consumption was very poor. Cell density and glutamate concentration were almost unaltered throughout the experiment and the culture reached the stationary phase within 8 days. The data are compared with earlier studies in which utilization of amino acids in Euglena gracilis was investigated. All tested amino acids (glutamate with limitations) were found to have the potential of being an alternative N-source for Euglena gracilis. Hence, these amino acids can be used as a non-toxic surrogate for (NH)HPO.
Keywords: Amino-acids; CELSS; Euglena gracilis; Nitrogen source

Changes in Gravitaxis and Gene-Expression in an Euglena gracilis Culture over Time - Krüger, Julia; Richter, Peter; Stoltze, Julia; Prasad, Binod; Strauch, Sebastian; Krüger, Marcus; Nasir, Adeel; Lebert, Michael (Biomolecules, 2024)
Age-dependent changes in the transcription levels of 5-day-old Euglena gracilis cells, which showed positive gravitaxis, 6-day-old cells without gravitactic orientation, and older cells (9- and 11-day-old, which displayed a precise negative gravitaxis) were determined through microarray analysis. Hierarchical clustering of four independent cell cultures revealed pronounced similarities in transcription levels at the same culture age, which proves the reproducibility of the cultivation method. Employing the non-oriented cells from the 6-day-old culture as a reference, about 2779 transcripts were found to be differentially expressed. While positively gravitactic cells (5-day-old culture) showed only minor differences in gene expression compared to the 6-day reference, pronounced changes of mRNAs (mainly an increase) were found in older cells compared to the reference culture. Among others, genes coding for adenylyl cyclases, photosynthesis, and metabolic enzymes were identified to be differentially expressed. The investigated cells were grown in batch cultures, so variations in transcription levels most likely account for factors such as nutrient depletion in the medium and self-shading. Based on these findings, a particular transcript (e.g., transcript 19556) was downregulated using the RNA interference technique. Gravitaxis and phototaxis were impaired in the transformants, indicating the role of this transcript in signal transduction. Results of the experiment are discussed regarding the increasing importance of E. gracilis in biotechnology as a source of valuable products and the possible application of E. gracilis in life-support systems.
CRIS-Team Scopus Importer:2024-04-05
Keywords: culture age; Euglena gracilis; gravitaxis; microarray analysis; phototaxis

Changes of Gene Expression in Euglena gracilis Obtained During the 29th DLR Parabolic Flight Campaign - Krüger, Julia; Richter, Peter; Stoltze, Julia; Strauch, Sebastian; Krüger, Marcus; Daiker, Viktor; Prasad, Binod; Sonnewald, Sophia; Reid, Stephen; Lebert, Michael (Scientific Reports, 2019)
Parabolic flight maneuvers of Novespace's Airbus A310 ZERO-G produce subsequent phases of hypergravity (about 20 s), microgravity (about 22 s) and another 20 s hypergravity on experiments located in the experiment area of the aircraft. The 29th DLR parabolic flight campaign consisted of four consecutive flight days with thirty-one parabolas each day. Euglena gracilis cells were fixed with TRIzol during different acceleration conditions at the first and the last parabola of each flight. Samples were collected and analyzed with microarrays for one-color gene expression analysis. The data indicate significant changes in gene expression in E. gracilis within short time. Hierarchical clustering shows that changes induced by the different accelerations yield reproducible effects at independent flight days. Transcription differed between the first and last parabolas indicating adaptation effects in the course of the flight. Different gene groups were found to be affected in different phases of the parabolic flight, among others, genes involved in signal transduction, calcium signaling, transport mechanisms, metabolic pathways, and stress-response as well as membrane and cytoskeletal proteins. In addition, transcripts of other areas, e.g., DNA and protein modification, were altered. The study contributes to the understanding of short-term effects of microgravity and different accelerations on cells at a molecular level.
CRIS-Team Scopus Importer:2019-10-15

Delayed fluorescence, steady state fluorescence, photosystem II quantum yield as endpoints for toxicity evaluation of Cu2+ and Ag+ - Strauch, Sebastian; Richter, Peter; Haag, Ferdinand; Krüger, Marcus; Krüger, Julia; Azizullah, Azizullah; Breiter, Roman; Lebert, Michael (Environmental and Experimental Botany, 2016)
The effect of copper and silver ions on photosynthetic parameters of the flagellate Euglena gracilis was determined. The photosystem II quantum yield (Y) and steady state fluorescence (F) were measured with a PAM-fluorometer, while delayed fluorescence (DF) was determined by means of a sensitive single-photon camera attached to an image analysis device, which counted the relative number of photons released from the algae in darkness after previous light-stimulation. We found that after 3 h of incubation photosynthesis was affected only in the presence of relatively high concentrations of the used noble metals. The obtained EC values for Cu were 505.8 mg L (Y ), 286.5 mg L (DF), and 491.0 mg L (F). The EC values for silver ions were 51.9 mg L (Y ), 51.8 mg L (DF) (values for F not determinable). Photosynthesis is far less sensitive against toxic noble metals compared to motility parameters as reported in earlier studies, in part because the organelles of photosynthesis, the chloroplasts, are well protected from external substances within the cell, while flagella, reaching into the surrounding of the cell, are more easily influenced. As chloroplasts are easily accessible by means of non-invasive methods e.g. PAM- fluorometry, they are probably interesting model systems in order to detect effects of substances deep inside the cell. Influence on the chloroplasts is a measure that a germicide entered the cells, diffused through the cytoplasm and the membranous systems and reached compartmentalized enzyme complexes.
Keywords: Delayed fluorescence; Ecotoxicology; Euglena gracilis; PAM-fluorometry; Photosynthetic yield; Steady state fluorescence

Eu:CROPIS - "Euglena gracilis: Combined Regenerative Organic-food Production in Space" - A Space Experiment Testing Biological Life Support Systems Under Lunar And Martian Gravity - Hauslage, Jens; Strauch, Sebastian; Essmann, Olaf; Haag, Ferdinand; Richter, Peter; Krüger, Julia; Stoltze, Julia; Becker, Ina; Nasir, Adeel; Bornemann, Gerhild; Mueller, Hartmut; Delovski, Toni; et al. (Microgravity Science and Technology, 2018)
Human space exploration needs stable life support systems for the supply of oxygen, water and food for each human explorer due to long term missions. The most promising approach for building stable life support systems is a combination of physico-chemical and biological systems. These hybrid systems combine the reliability of physico-chemical and the sustainability of biological life support systems. Also the disadvantages, which are the finite resources of physico-chemical and the imperfect reliability of biological systems, are mutually balanced. To improve the reliability of biological life support systems, a combination of different biological systems may stabilize the whole approach during long term operations. The satellite mission Eu:CROPIS (Euglena gracilis: Combined Regenerative Organic-food Production In Space) is a testbed for investigating the behavior of combined biological life support systems under the influence of altered gravity, here, Lunar and Martian gravity. The core systems are a biological trickle filter for processing urine into a fertilizer solution via nitrification and Euglena gracilis, a photosynthetic protist which is able to produce oxygen and biomass while protecting the whole system against high ammonia concentrations.
Keywords: Compact satellite; Life support system; Moon; Mars; Reduced gravity; Nitrification